USULAN PENGEMBANGAN APLIKASI PT SOLUSI BERDASARKAN IDENTIFIKASI KEBUTUHAN APLIKASI PENCARIAN PEKERJA KERAH BIRU - Meliani Sembiring M., Rebecca
The high demand for recruiting blue-collar workers and the rapid evolution of technology have led to a shift in the recruitment process towards online platforms, including third-party portals. Therefore, PT Solusi (pseudonym) has launched a blue-collar worker search application. However, the application is predicted to fall short of achieving its market dominance target, which is a minimum of one percent of the serviceable obtainable market within two to four years after its release. Consequently, improvement strategies are required to enhance recruiter adoption. Considering the product's introductory stage and its flexibility for app enhancements, this research aims to formulate improvement proposals while considering user satisfaction regarding the fulfillment of current application attributes and capabilities. Potential users of the Solusi application are corporate recruiters seeking blue-collar workers who have already digitized their recruitment processes. In this study, qualitative identification of required attributes was conducted through interviews with eight respondents, and a critical incident technique (CIT) questionnaire was administered to 95 potential users. Eighteen required attributes were selected for